Alterations in cellular metabolism under different grades of glioma staging identified based on a multi-omics analysis strategy - Yan, Xianlei; Li, Jinwei; Zhang, Yang; Liang, Cong; Liang, Pengcheng; Li, Tao; Liu, Quan; Hui, Xuhui (Frontiers in Endocrinology, 2023)
Glioma is a type of brain tumor closely related to abnormal cell metabolism. Firstly, multiple combinatorial sequencing studies have revealed this relationship. Genomic studies have identified gene mutations and gene expression disorders related to the development of gliomas, which affect cell metabolic pathways. In addition, transcriptome studies have revealed the genes and regulatory networks that regulate cell metabolism in glioma tissues. Metabonomics studies have shown that the metabolic pathway of glioma cells has changed, indicating their distinct energy and nutritional requirements. This paper focuses on the retrospective analysis of multiple